Nanotechnology-Based Antimicrobial Surface-Coating Technologies and Their Potential Applications - Gökhan Gurur Gökmen; Duygu Kışla (Turkish Journal of Agriculture: Food Science and Technology, 2022)
Nanotechnology has a wide study field including organic and/or inorganic particles smaller than 100 nanometers and all kinds of technological studies developed using these particles. In the production of nanoparticles, top-down approaches in which macro-sized materials were reduced to nano-sizes and bottom-up approaches in which atoms / molecules were increased to nano-sizes by different chemical reactions, are used. Currently, nanoparticles produced by top-down approaches might be used in many industries such as food industry, water treatment systems, cosmetics, and medicine. Microorganisms that tend to move, adhere, and colonize a solid surface, cause the formation of microbial biofilm on these surfaces. Microbial biofilms show high resistance to traditional antimicrobial applications in industrial environments especially where food is processed, water piping systems, biological tissues and medical implants. Therefore, the requirement has emerged to make not only the surfaces in direct contact with people, but also the surfaces in contact with food, to be resistant to microorganisms by different antimicrobial coating techniques. In this review, it is aimed to give information about the production methods of nanomaterials, different antimicrobial surface-coating techniques, the mechanism of antimicrobial nanoparticles on microorganisms and potential applications of antimicrobial surfaces.